The prevalence of insomnia in the general population in China: A meta-analysis - Cao, Xiao-Lan; Wang, Shi-Bin; Zhong, Bao-Liang; Zhang, Ling; Ungvari, Gabor S.; Ng, Chee H.; Li, Lu; Chiu, Helen F. K.; Lok, Grace K. I.; Lu, Jian-Ping; Jia, Fu-Jun; Xiang, Yu-Tao (PloS one, 2017)
This is the first meta-analysis of the pooled prevalence of insomnia in the general population of China. A systematic literature search was conducted via the following databases: PubMed, PsycINFO, EMBASE and Chinese databases (China National Knowledge Interne (CNKI), WanFang Data and SinoMed). Statistical analyses were performed using the Comprehensive Meta-Analysis program. A total of 17 studies with 115,988 participants met the inclusion criteria for the analysis. The pooled prevalence of insomnia in China was 15.0% (95% Confidence interval [CI]: 12.1%-18.5%). No significant difference was found in the prevalence between genders or across time period. The pooled prevalence of insomnia in population with a mean age of 43.7 years and older (11.6%; 95% CI: 7.5%-17.6%) was significantly lower than in those with a mean age younger than 43.7 years (20.4%; 95% CI: 14.2%-28.2%). The prevalence of insomnia was significantly affected by the type of assessment tools (Q = 14.1, P = 0.001). The general population prevalence of insomnia in China is lower than those reported in Western countries but similar to those in Asian countries. Younger Chinese adults appear to suffer from more insomnia than older adults. CRD 42016043620.